A class of shape optimization problems for some nonlocal operators - Fernandez Bonder, Julian (2017)
In this work we study a family of shape optimization problem where the state equation is given in terms of a nonlocal operator. Examples of the problems considered are monotone combinations of fractional eigenvalues. Moreover, we also analyze the transition from nonlocal to local state equations.